Education Administration Perspective Policy Makers and Educational Institutions - Asma Niah (CV. ADIBA AISHA AMIRA, 2022)
Education Administration is a process or effort to achieve an educational goal by taking into account various components of education so that it can improve the education system by utilizing various tools to support learning and teaching activities. The scope of education administration is not just school administration or learning administration. Such a view is a narrow view. Education administration is broader than that, although the estuary of all policies is an educational unit at all levels and types. So education administration is at the level of policy makers and at the level of education units. Educational administration is the science of structuring human resources, curriculum or learning resources and facilities to achieve educational goals optimally and create an agreed-upon atmosphere for humans. Doubts about the function of the school as the best place for learning are still doubted by several related parties, and facts regarding the capacity building program have failed to hone the skills of teachers, which has resulted in the poor quality of the learning they have built